Azanitrile Inhibitors of the SmCB1 Protease Target Are Lethal to Schistosoma mansoni: Structural and Mechanistic Insights into Chemotype Reactivity - Jílková, Adéla; Horn, Martin; Fanfrlík, Jindřich; Küppers, Jim; Pachl, Petr; Řezáčová, Pavlína; Lepšík, Martin; Fajtová, Pavla; Rubešová, Petra; Chanová, Marta; Caffrey, Conor R; Gütschow, Michael; et al. (ACS infectious diseases, 2021)
Azapeptide nitriles are postulated to reversibly covalently react with the active-site cysteine residue of cysteine proteases and form isothiosemicarbazide adducts. We investigated the interaction of azadipeptide nitriles with the cathepsin B1 drug target (SmCB1) from Schistosoma mansoni, a pathogen that causes the global neglected disease schistosomiasis. Azadipeptide nitriles were superior inhibitors of SmCB1 over their parent carba analogs. We determined the crystal structure of SmCB1 in complex with an azadipeptide nitrile and analyzed the reaction mechanism using quantum chemical calculations. The data demonstrate that azadipeptide nitriles, in contrast to their carba counterparts, undergo a change from E- to Z-configuration upon binding, which gives rise to a highly favorable energy profile of noncovalent and covalent complex formation. Finally, azadipeptide nitriles were considerably more lethal than their carba analogs against the schistosome pathogen in culture, supporting the further development of this chemotype as a treatment for schistosomiasis.
Keywords: schistosomiasis; cysteine proteases; Cathepsin B; azapeptide inhibitors; structure−activity relationships; Animals; protein structures; kathepsin B; proteasy; Schistosoma mansoni; zvířata; Peptide Hydrolases